2003
DOI: 10.1128/iai.71.2.1008-1010.2003
|View full text |Cite
|
Sign up to set email alerts
|

Migration through the Extracellular Matrix by the Parasitic ProtozoanLeishmaniaIs Enhanced by Surface Metalloprotease gp63

Abstract: Leishmania species engineered to express high levels of the surface metalloprotease gp63 have enhanced capacity of migration through extracellular matrix in vitro. This correlates with gp63 degradation of extracellular matrix components, such as collagen type IV and fibronectin, and suggests an important role for gp63 in the pathogenesis of leishmaniasis.Leishmania species are digenetic protozoa that alternately parasitize their sand fly vectors and mammalian macrophages. Parasites are deposited in the mammali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
115
0
6

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(124 citation statements)
references
References 17 publications
2
115
0
6
Order By: Relevance
“…Thrice-washed cells were fixed in 0.5% glutaraldehyde (Glu) in phosphate-buffered saline (PBS) for 30 min on ice and then washed and resuspended at 10 8 per ml. It has been previously shown that the Glu fixation of cells does not significantly diminish the surface proteolytic activity of leishmanolysin (16)(17)(18). Purified bovine FN and laminin (LM) were purchased from a commercial source (Sigma-Aldrich), divided into aliquots, and stored at Ϫ20°C prior to use.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thrice-washed cells were fixed in 0.5% glutaraldehyde (Glu) in phosphate-buffered saline (PBS) for 30 min on ice and then washed and resuspended at 10 8 per ml. It has been previously shown that the Glu fixation of cells does not significantly diminish the surface proteolytic activity of leishmanolysin (16)(17)(18). Purified bovine FN and laminin (LM) were purchased from a commercial source (Sigma-Aldrich), divided into aliquots, and stored at Ϫ20°C prior to use.…”
Section: Methodsmentioning
confidence: 99%
“…The surface biotinylation and preparation of detergent lysates of L. amazonensis were done as described previously (18,19). Briefly, the biotinylation of parasite surface proteins (using 10 7 washed, live cells) or 10 to 50 mg of FN or LM was done by incubation in PBS containing 1 mg/ml of EZ-Link N-hydroxysulfosuccinimide-long chain-biotin reagent (Pierce) on ice for 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This major surface antigen exerts several functions before and after internalisation by phagocytic cells. It has been shown to degrade the extracellular matrix at a sub-cutaneous level, which is believed to facilitate the parasite movement under the skin following inoculation of promastigotes into the dermis [11]. GP63 is also able to inhibit complement activity by binding C3b and to increase the conversion of C3b into C3bi, an inactive form of C3, through direct cleavage, and thereby reducing fixation of the terminal C5-C9 membrane attack complex [12].…”
Section: -Complement and Galectinmentioning
confidence: 99%